Negara Madinah sebagai Cerminan Awal Penerapan Nilai-Nilai Konstitusional dalam Bingkai Pancasila - Kuntes Nasution (Kamali: Jurnal Ilmu Agama, 2025)
The Medina Charter, formulated by the Prophet Muhammad, is seen as an early model for the application of constitutional principles emphasizing justice, deliberation, respect for diversity, and the protection of citizens’ rights. The urgency of this research lies in its relevance to Pancasila, the foundation of the Indonesian state, which prioritizes the values of divinity, humanity, unity, democracy, and social justice. This research aims to examine the compatibility of the constitutional principles of the Medina Charter with the values of Pancasila and to assess its contribution to strengthening the Indonesian state system. The method used is qualitative-descriptive research with a historical approach and content analysis of the text of the Medina Charter, philosophical documents of Pancasila, and related academic literature. The results of the study indicate that the value of justice in the Medina Charter aligns with the fifth principle of Pancasila, the principle of national unity is reflected in the third principle, religious freedom is aligned with the first principle, the deliberation system reflects the fourth principle, and respect for individual and group rights is in accordance with the second principle. In conclusion, the State of Medina can be seen as a historical reference as well as a normative inspiration in strengthening the constitutional understanding of Pancasila, thus demonstrating the continuity of universal values between Islamic tradition and the foundation of the Indonesian state.